Short-term effect of intravenous methylprednisolone pulse therapy on glycemic control in patients with normoglycemia and pre-diabetes - Mitkowska, Katarzyna; Pelewicz, Katarzyna; Walasik, Izabela; Szewczyk, Sebastian; Miśkiewicz, Piotr (Journal of Medical Science, 2020)
Introduction. Systemic steroid therapy leads to disturbances in carbohydrate metabolism. The effect of immunosuppression with intravenous methylprednisolone (IVMP) pulses on glycaemia is not conclusive. Aim. This study aimed to assess the short-term effect of IVMP therapy in moderate-to-severe Graves’ orbitopathy (GO) on glycaemic control in normoglycaemic patients with and without pre-diabetes. Material and Methods. Twenty-five GO patients treated with IVMP pulses (at initial dose of 6 x 0.5 g once a week, followed by 0.25 g given for 6 consecutive weeksweekly) were recruited and divided into a normoglycaemic group (n = 15, patients without pre-diabetes) and a pre-diabetic group (n = 10, patients with impaired fasting glycaemia (IFG) and/or impaired glucose tolerance (IGT)). Six daily capillary blood glucose measurements were performed at fixed times the day before and on the day of the first pulse administration. Results. There was a significant increase in the glucose concentration on the day of IVMP administration in both groups of patients compared to the day before drug administration, with 50% of patients showing an increase in blood glucose above 200 mg/dl. There were no statistically significant differences between the two groups. Conclusions. Methylprednisolone in a high intravenous dose has a tremendous impact on the blood glucose level in normoglycaemic and pre-diabetic patients on the day of drug administration.